IMPROVING PHONEMIC AWARENESS AND READING FLUENCY IN YOUNG ESL LEARNERS THROUGH GOOGLE READ ALONG - Ismail, Nor Irnahanis Sofia; Ismail, Hanita Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The growing demand for effective early literacy interventions among young English as a Second Language (ESL) learners highlights the need for accessible, engaging, and pedagogically sound digital tools. Many children in multilingual and low-resource settings face challenges in developing foundational reading skills particularly phonemic awareness and fluency due to limited access to qualified teachers and learning materials. This study adopts a systematic literature review design, conducted in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) framework, to evaluate the effectiveness of Google Read Along, a speech-based digital reading application, in enhancing phonemic awareness and reading fluency among young ESL learners. The review followed four structured phases identification, screening, eligibility, and inclusion/exclusion across five major academic databases: ERIC, Scopus, JSTOR, SpringerLink, and Google Scholar. Search strings combined targeted keywords with Boolean operators, and strict inclusion criteria limited the scope to 25 peer-reviewed empirical studies published between 2019 and 2024 that focused on ESL learners aged 5–12 and directly employed Google Read Along as an intervention. Exclusion criteria ruled out studies involving first-language English speakers, non-speech-based tools, non-empirical research, and non-English publications. Thematic analysis of the selected studies revealed five recurring themes: (1) digital tools for enhancing phonemic awareness, (2) reading fluency development through repetition and feedback, (3) learner engagement and motivation in ESL contexts, (4) accessibility and equity in low-resource settings, and (5) the evolving role of teachers in digital integration. Overall, findings suggest that Google Read Along is a promising tool for supporting early literacy in ESL learners, particularly when integrated with complementary instructional strategies. The results offer evidence-based insights for educators, curriculum developers, and policymakers seeking to strengthen early literacy programs through technology integration.